1999
DOI: 10.1007/s000660050060
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Radiotherapy for Painful Bone Metastases

Abstract: Based on this review of literature data concerning randomized trials a treatment with a single dose of 8 Gy is effective for inducing pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2000
2000
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
(46 reference statements)
0
3
0
4
Order By: Relevance
“…Furthermore, the comparison of efficiency of a single dose with fractionated radiotherapy for painful bone metastases showed the similar palliation pain effect [9,10]. Koswig & Budach [11] observed more effective recalcification of bone metastases after using the fractionation schedule of palliative radiotherapy than after single dose radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the comparison of efficiency of a single dose with fractionated radiotherapy for painful bone metastases showed the similar palliation pain effect [9,10]. Koswig & Budach [11] observed more effective recalcification of bone metastases after using the fractionation schedule of palliative radiotherapy than after single dose radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that methodological differences between the reports seem to contribute to unclear results with respect to pain relief, complete pain relief and duration of pain relief. One additional report dealt with the same issue, re-investigating 10 RCTs (38). Four out of these 10 studies have been published since 1994 (20, 23 Á/25).…”
Section: Radiotherapy (Rt)mentioning
confidence: 99%
“…innerhalb der ersten sechs Wochen nach der Radiotherapie erreicht. Dieser kann nach Literaturangaben bereits nach einer Dosis von 10 bis 20 Gy erreicht werden [16]; vergleichbar ist aus der radiotherapeutischen Behandlung ossärer Metastasen bei soliden Tumoren bekannt, dass hypofraktionierte, niedrig dosierte Schemata (zum Beispiel 1-mal 8 Gy, 4-mal 4 Gy, 4-mal 5 Gy) zu einer adäquaten Schmerzlinderung führen [8,12,14,15]. Aufgrund der fehlenden Variationsbreite in den von uns verwendeten Dosierungen können wir diesbezüglich jedoch nicht Stellung nehmen.…”
Section: Analgetischer Effektunclassified